Correction: A next generation vaccine against human rabies based on a single dose of a chimpanzee adenovirus vector serotype C. - Federico Napolitano; Rossella Merone; Adele Abbate; Virginia Ammendola; Emma Horncastle; Francesca Lanzaro; Marialuisa Esposito; Alessandra Maria Contino; Roberta Sbrocchi; Andrea Sommella; Joshua D Duncan; Joseph Hinds; et al. (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0008459.].